Molecular detection of Mycobacterium leprae in the lachrymal film of leprosy cases, health staff, and healthy individuals - Josmar Sabage; Luís E Sabage; Andrea FF Belone; Gislaine A Querino; Luciana R Fachim; Luiza Pinheiro; Marcos CL Virmond (Journal of Infection in Developing Countries)
Introduction: Leprosy is still endemic in some countries, and interruption of the infection chain is essential to reduce its burden. This article aims to verify if the lachrymal film of leprosy cases and non-leprosy can be a site of relevance in the early molecular detection of M. leprae.